In silico exploration of phytoconstituents of Enicostemma littorale as potential DPP-4 inhibitors for the treatment of type 2 diabetes mellitus (International Journal of Food and Nutritional Sciences, 2022)
The goal of the current investigation was to use a computational technique to examine the DPP-4 inhibitory potential of phytoconstituents of E. littorale. The Lipinski rule of five, the Veber's rule, and the ADMET characteristics have all been used to filter all of the phytoconstituents. Only a few compounds were chosen from this first screening to conduct molecular docking experiments on the DPP-4 enzyme: Apigenin, Ferulic acid, Genkwanin, p-coumaric acid, Protocatechuic acid, Syringic acid, and Vanillic acid. The native ligand had a binding free energy of -9.1 kcal/mol and a beneficial way of binding into the enzyme's allosteric site, while it also created four hydrogen bonds with Tyr662, Arg125, Arg358 and Phe357. In comparison to the native ligand, apigenin, ferulic acid, p-coumaric acid, protocatechuic acid, syringic acid, and vanillic acid formed more hydrogen bonds and had binding free energies that were, respectively, -8.7, -6.4, -6.1, -5.7, and -6.1 kcal/mol, indicating stronger DPP-4 inhibition. The formation of hydrogen bonds with allosteric amino acid residues by apigenin, ferulic acid, p-coumaric acid, protocatechuic acid, syringic acid, and vanillic acid with these phytoconstituents indicates their effective enzyme inhibition. E. littorale extract, which is previously recognised to have therapeutic benefits in diabetic patients, is a common ingredient in anti-diabetic Ayurvedic preparations. We discovered and described the primary phytochemical with the antidiabetic potential.